Pengembangan Kompetensi Siswa Melalui Program Kampus Mengajar Videografi : Studi Kasus Di SMK Negeri 5 Palangka Raya - Neny Fidayanti; Noormalina Martina; Lidia Natalia; Destian Noor Adyatma; Muhammad Hairil Ali Mesir; Yoel Garcia Kairupan; Rizka Anisyaputri; Melka Melka (Universitas Negeri Gorontalo, 2026)
The Campus Teaching Program Batch 3 was implemented at SMKN-5 Palangka Raya as an implementation of the Independent Learning Campus (MBKM) policy. This study aims to analyze the implementation and impact of student work programs in improving the quality of learning in vocational schools. The research method used a qualitative approach with participatory observation techniques for the period of October 6 to December 15, 2025. One of the work programs implemented at SMKN 5 Palangka Raya was basic videography learning in class XI DKV. The results of this learning showed that this activity successfully improved the competency of DKV students majoring in videography. Collaboration between students, supervising lecturers, mentor teachers, and the school was the key to the successful implementation of the program.